POTENSI INHIBITOR α-GLUKOSIDASE EKSTRAK KASAR Streptomyces tendae SEBAGAI PENURUN KADAR GLUKOSA DARAH PADA TIKUS Sprague Dawley DIABETES: The Potency of Streptomyces tendae Crude Extract as an α-Glucosidase Inhibitor in Lowering Blood Glucose Levels of Diabetic Sprague Dawley Rats - Aliful Karim; Min Rahminiwati; Yulin Lestari (Jurnal Sumberdaya Hayati, 2026)
Diabetes is a disease caused by insulin dysfunction or impaired insulin production, leading to elevated blood glucose levels (hyperglycemia). It is classified into three types: Type 1, Type 2, and Gestational Diabetes Mellitus (GDM). Type 2 diabetes is a condition resulting from insulin resistance. Previous research has identified microorganisms isolated from Ficus deltoidea that produce α-glucosidase inhibitors. This study aims to determine the potential of extracts derived from Streptomyces tendae as an α-glucosidase inhibitor through both in-vitro and in-vivo assessments, specifically evaluating the extract's effectiveness in reducing blood glucose levels in Sprague Dawley rats with Type 2 diabetes. Although the isolates from previous studies showed a decrease in activity, they remained capable of lowering blood glucose levels in the rats. Statistical analysis of the Oral Glucose Tolerance Test (OGTT) provided sufficient evidence to conclude that the combination of time (minutes) and extract administration significantly influenced the reduction of blood glucose levels in diabetic rats (P<0.05). Diabetes was induced in the rats using low-dose streptozotocin. The results showed that "Dose 1" of the extract significantly reduced blood glucose levels compared to control (aquades) treatment starting from the fifth day of administration and was effective in suppressing further increases in blood sugar (P<0.05).